Sign effect in adolescents: Within‐subject comparison of delay discounting of hypothetical monetary gains and losses - Furrebøe, Elise Frølich (Journal of the experimental analysis of behavior, 2020)
The purpose of this article is to contribute to the research on the sign effect, steeper discounting of gains compared to losses, by offering results from an experiment using a “double‐delay” procedure on adolescents. Twenty‐four 14‐year‐old schoolchildren completed a computer‐based test consisting of choices of Smaller–Sooner (SS) and Larger–Later (LL) hypothetical monetary gains and losses. Within‐subject comparison and analysis of the aggregated data were conducted. Current results were also examined in light of prior research with adult participants, and variations in behavioral patterns were identified. Although the sign effect appears to be more profound in adolescents compared to adults, the effect of immediacy persists regardless of the sign of the outcome, and zero discounting of losses is often the case, suggesting that the sign effect is driven largely by qualitative differences.